Proceso pedagógico para el desarrollo de habilidades motrices básicas en futbolistas de la Escuela Francisco Robles - Herrera Yaguana, Jorge Eduardo (2025)
The main objective of this thesis was the design of a pedagogical guide aimed at the promotion of basic motor skills in the students of the “Francisco Robles” School. This work focused on the improvement of the infants' motor skills, an essential aspect for their performance in soccer and, in general terms, for their physical and motor development. To achieve this, several objectives were set, such as inquiries about the theoretical and methodological references that support the development of basic motor skills, offering an extensive understanding of the best pedagogical practices in the area. Subsequently, a diagnosis of the current state of the children's motor skills was carried out through direct observation and the application of motor skills evaluations. Based on these results, a pedagogical guide was prepared, which offers strategies and exercises applied to collaborate with students in the acquisition of motor skills. The guide was designed to be clear and easily understood by physical education educators, allowing its integration into the regular sessions of the educational institution. The population consisted of 34 individuals. For the study, a sample of 20 students from the “Francisco Robles” School was selected intentionally, together with the 4 physical education teachers, resulting in a total of 24 participants. These individuals were fundamental for the collection of data and the subsequent evaluation of the viability of the guide, providing a valuable pedagogical resource that facilitates the teaching-learning process of motor skills, optimizing not only their performance in soccer, but also their complete physical development.